CD226 Is Required to Maintain Megakaryocytes/Platelets Homeostasis in the Treatment of Knee Osteoarthritis With Platelet-Rich Plasma in Mice - Liu, Yongming; Zhang, Yuan; Zhang, Jinxue; Ma, Jingchang; Bian, Ka; Wang, Yuling; Xu, Xuexue; Wu, Shuwen; Cheng, Kun; Zhang, Yun; Ding, Yong; Zhou, Yong; et al. (Frontiers in Pharmacology, 2021)
Platelet-rich plasma (PRP) is a platelet-based application used to treat osteoarthritis (OA) clinically. The co-stimulatory molecule CD226 is expressed in T cells, NK cells, and also platelets. However, exact effects of CD226 on platelets and whether its expression level influences PRP efficacy are largely unknown. Here, CD226fl/flPF4-Cre mice were obtained from mating CD226 fl/fl mice with PF4-Cre mice. Blood samples and washed platelets were collected from the mice eyeballs to undergo routine blood tests and transmission electron microscopy. Differentially expressed proteins were detected by iTRAQ-based proteomics analysis. Animal OA models were established through surgical destabilization of the medial meniscus (DMM) for C57BL/6 wildtype mice, followed by PRP injection to evaluate the effects of platelet CD226 on PRP efficacy. The results showed that deletion of platelet CD226 increased the number of megakaryocytes (MKs) in bone marrow (BM) but reduced MKs in spleen, combined with significantly decreased platelet amounts, α-granule secretion, and reduced immature platelets; indicating that absence of platelet CD226 may disrupt MK/platelet homeostasis and arrested platelet release from MKs. Sequencing analysis showed abnormal ribosomal functions and much downregulated proteins in the absence of platelet CD226. Autophagy-related proteins were also reduced in the CD226-absent MKs/platelets. Moreover, deletion of platelet CD226 diminished the protective effects of PRP on DMM-induced cartilage lesions in mice, and PDGF restored it. Therefore, deficiency of platelet CD226 inhibited platelet maturation, secretion, and normal ribosomal functions, which may lead to depressed PRP efficacy on OA, suggesting that CD226 is required to regulate platelet growth, functions, and its application.